Phylogenetic position reevaluation of Kyrtuthrix and description of a new species K. huatulcensis from Mexico´s Pacific coast - León-Tejera, Hilda P.; González-Resendiz, Laura; Johansen, Jeffrey R.; Segal-Kischinevsky, Claudia; Escobar, Viviana; Alba Lois, Luisa (Phytotaxa, 2016)
Benthic marine heterocytous cyanoprokaryotes of Mexico´s tropical coast are being recognized as an important and conspicuous component of the supralittoral and intertidal zones usually described as an extreme and low diversity biotope. Although Kyrtuthrix has been reported from different coasts worldwide, its complex morphology has led to differing taxonomic interpretations and positioning. Ten marine supra and intertidal populations of Kyrtuthrix were analyzed using a detailed morphological approach, complemented with ecological and geographical information as well as DNA sequence data of the 16S rRNA gene and associated 16S–23S ITS. Kyrtuthrix huatulcensis is described as a new species, different from K. dalmatica Ercegovic and K. maculans (Gomont) Umezaki based primarily on morphological data. Our material has smaller dimensions in thalli, filaments, trichomes and cells, and possesses differences in qualitative characters as well. Our material is epilithic as in K. maculans but not endolithic as in K. dalmatica. The analysis of molecular data, mainly 16S rRNA gene sequence, show that this genus is within the Rivulariaceae clade, and outside of the Scytonemataceae clade. ITS secondary structure comparison with some of the closer representatives of Rivulariaceae shows considerable differences with these related genera. Based on the evidence gathered in this study, inclusion of Kyrtuthrix within the Rivulariaceae, rather than the Scytonemataceae, is fully supported.